\(\ne\)c) và \(\frac{1}{c}=\...">
K
Khách

Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.

26 tháng 12 2017

\(\frac{1}{c}=\frac{1}{2}.\left(\frac{1}{a}+\frac{1}{b}\right)\)

\(\frac{1}{c}:\frac{1}{2}=\frac{1}{a}+\frac{1}{b}\)

\(\frac{2}{c}=\frac{b}{ab}+\frac{a}{ab}\)

\(\frac{2}{c}=\frac{a+b}{ab}\)

\(2ab=\left(a+b\right)c\)

\(ab+ab=ac+bc\)

\(ac-ab=ab-bc\)

\(a.\left(c-b\right)=b.\left(a-c\right)\)

\(\Rightarrow\frac{a}{b}=\frac{a-c}{c-b}\)

26 tháng 12 2017

https://goo.gl/BjYiDy

6 tháng 1 2017

ta có: \(\frac{1}{c}=\frac{1}{2}\left(\frac{1}{a}+\frac{1}{b}\right)\)

\(=\frac{1}{c}\times2=\frac{1}{a}+\frac{1}{b}\)

\(=\frac{2}{c}=\frac{1}{a}+\frac{1}{b}\)

\(=\frac{2}{c}=\frac{b+a}{ab}\)

= \(c\left(b+a\right)=ab\times2\)

= cb +ca = ab+ab

= ab - cb = ac-ab

\(=b\left(a-c\right)=a\left(c-b\right)\)

= \(\frac{a}{b}=\frac{a-c}{c-b}\)

6 tháng 1 2017

\(\frac{1}{c}=\frac{1}{2}\left(\frac{1}{a}+\frac{1}{b}\right)\)

\(\frac{1}{c}=\frac{1}{2a}+\frac{1}{2b}\)

\(\frac{1}{c}=\frac{a+b}{2ab}\)

\(2ab=c\left(a+b\right)\)

\(ab+ab=ac+bc\)

\(ab-bc=ac-ab\)

\(b\left(a-c\right)=a\left(c-b\right)\)

\(\Rightarrow\frac{a}{b}=\frac{a-c}{c-b}\left(đpcm\right)\)

21 tháng 12 2019

Từ \(\frac{1}{c}=\frac{1}{2}\left(\frac{1}{a}+\frac{1}{b}\right)\Rightarrow\frac{1}{c}=\frac{1}{2}\left(\frac{a+b}{ab}\right)\)

\(\Rightarrow\frac{1}{c}=\frac{a+b}{2ab}\)

\(\Rightarrow2ab=c.\left(a+b\right)\)

\(\Rightarrow ab+ab=ac+bc\)

\(\Rightarrow ab-bc=ac-ab\)

\(\Rightarrow b.\left(a-c\right)=a.\left(c-b\right)\)

\(\Rightarrow\frac{a}{b}=\frac{a-c}{c-b}\)

5 tháng 1 2018

Từ \(gt\Leftrightarrow\frac{1}{c}=\frac{1}{2}.\frac{a+b}{ab}\)

\(\Leftrightarrow\frac{1}{c}=\frac{a+b}{2ab}\Leftrightarrow c\left(a+b\right)=2ab\Leftrightarrow ac+bc=ab+ab\)

\(\Leftrightarrow ac-ab=ab-bc\Leftrightarrow a\left(c-b\right)=b\left(a-c\right)\)

\(\Rightarrow\frac{a}{b}=\frac{a-c}{b-c}\) (đpcm)

5 tháng 7 2019

Từ \(gt\Leftrightarrow\frac{1}{c}=\frac{1}{2}.\frac{a+b}{ab}\)

\(\Leftrightarrow\frac{1}{c}=\frac{a+b}{2ab}\Leftrightarrow c\left(a+b\right)=2ab\Leftrightarrow ac+bc=ab+ab\)

\(\Leftrightarrow ac-ab=ab-bc\Leftrightarrow a\left(c-b\right)=b\left(a-c\right)\)

\(\Rightarrow\frac{a}{b}=\frac{a-c}{b-c}\)

\(\Rightarrowđpcm\)

2 tháng 2 2017

theo bài ra ta có:

\(\frac{1}{c}=\frac{1}{2}\left(\frac{1}{a}+\frac{1}{b}\right)\)

\(\Rightarrow\frac{1}{c}=\frac{1}{2}\left(\frac{b}{ab}+\frac{a}{ab}\right)\\ \Rightarrow\frac{1}{c}=\frac{1}{2}.\frac{a+b}{ab}\\ \Rightarrow\frac{1}{c}=\frac{a+b}{2ab}\)

=> 2ab = c(a + b)

=> ab + ab = ca + cb

=> ab - cb = ca - ab

=> b( a - c ) = a( c - b )

=> \(\frac{a}{b}=\frac{a-c}{c-b}\left(đpcm\right)\)

14 tháng 12 2017

\(\frac{1}{c}=\frac{1}{2}\left(\frac{1}{a}+\frac{1}{b}\right)\)

\(\frac{1}{c}=\frac{1}{2}\left(\frac{a+b}{ab}\right)\)

\(\Rightarrow2ab=c\left(a+b\right)\)

\(\Rightarrow ab+ab=ca+bc\)

\(\Rightarrow ab-cb=ac-ab\)

\(\Rightarrow b\left(a-c\right)=a\left(c-b\right)\)

\(\Rightarrow\frac{a}{b}=\frac{a-c}{c-b}\)

Trả lời :........................................................

\(\Rightarrow\frac{a}{b}=\frac{a-c}{c-b}......................\)

Hk tốt,,,,,,,,,,,,,,,,,,,,,,,,,,,,,,,,,,,,,,,,,,,,,,,,,

Học sinh giỏi 6A

2 tháng 12 2019

Ta có: \(\frac{1}{c}=\frac{1}{2}\left(\frac{1}{a}+\frac{1}{b}\right)\)

\(\Rightarrow\frac{1}{c}\div\frac{1}{2}=\frac{1}{a}+\frac{1}{b}\)

\(\Rightarrow\frac{2}{c}=\frac{b+a}{ab}\)

\(\Rightarrow2ab=c\left(b+a\right)\)

\(\Rightarrow ab+ab=bc+ac\)

\(\Rightarrow ab-bc=ac-ab\)

\(\Rightarrow b\left(a-c\right)=a\left(c-b\right)\)

\(\Rightarrow\frac{a}{b}=\frac{a-c}{c-b}\)(đpcm)